1997
DOI: 10.1002/(sici)1097-4628(19970425)64:4<707::aid-app10>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization kinetics of compatibilized blends of a liquid crystalline polymer with polypropylene

Abstract: Blends of a maleic anhydride-grafted polypropylene (m-PP) and a liquid crystalline polymer (LCP) based on a copolyester of hydroxynapthoic acid and hydroxybenzoic acid were fabricated. The morphology and isothermal and nonisothermal crystallization kinetics behavior of the m-PP copolymer and m-PP/LCP blends were investigated using polarizing optical microscopy, depolarized light intensity, and differential scanning calorimetry. A polarizing optical micrograph revealed that the m-PP is very effective to promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 9 publications
2
12
0
Order By: Relevance
“…Representative surfaces of the cryogenically fractured iPP/Vectra blends are shown in Figure 1. According to previous results,15, 16, 29, 43 in these micrographs, it can be seen that the blends consist of two separate phases, indicating that the polymers were not miscible. The Vectra domains appeared in the iPP matrix in the form of small spherical droplets, probably due to a low degree of shearing during blend processing.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Representative surfaces of the cryogenically fractured iPP/Vectra blends are shown in Figure 1. According to previous results,15, 16, 29, 43 in these micrographs, it can be seen that the blends consist of two separate phases, indicating that the polymers were not miscible. The Vectra domains appeared in the iPP matrix in the form of small spherical droplets, probably due to a low degree of shearing during blend processing.…”
Section: Resultssupporting
confidence: 69%
“…It has been widely observed that the crystallization of iPP generally occurs on the surface of heterogeneities. At present, many organic and inorganic substances,5, 25–28 mainly of low molecular weight, have been reported as efficient nucleating agents for α or β modifications of iPP; however, information on the role that LCPs have on iPP nucleation and the polymorphic modifications obtained for iPP is scarce 29, 30…”
Section: Introductionmentioning
confidence: 99%
“…If a high density of nucleation sites prevails, a columnar growth known as transcrystallinity will develop and enclose the fiber. Transcrystallinity can be induced in PP composites reinforced with fibers under the appropriate conditions 22, 24, 25. Transcrystallinity at the fiber–matrix interface can facilitate stress transfer more efficiently.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, considerable interest has been devoted to the study of crystallization rates, morphologies, crystal structures and mechanical properties of blends of compatible and incompatible polymers in order to understand and improve the properties of polymers 1–6. Studying the non‐isothermal crystallization of polymers is of great technological significance, since most practical processing techniques are carried out under non‐isothermal conditions.…”
Section: Introductionmentioning
confidence: 99%